2021
DOI: 10.3389/fpls.2021.752790
|View full text |Cite
|
Sign up to set email alerts
|

Residue 49 of AtMinD1 Plays a Key Role in the Guidance of Chloroplast Division by Regulating the ARC6-AtMinD1 Interaction

Abstract: Chloroplasts evolved from a free-living cyanobacterium through endosymbiosis. Similar to bacterial cell division, chloroplasts replicate by binary fission, which is controlled by the Minicell (Min) system through confining FtsZ ring formation at the mid-chloroplast division site. MinD, one of the most important members of the Min system, regulates the placement of the division site in plants and works cooperatively with MinE, ARC3, and MCD1. The loss of MinD function results in the asymmetric division of chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Since ARC3 is the core component of the Min system, the J-like domain is likely to regulate the interaction between ARC6 and other Min components as well. It has been reported that ARC6 interacts with both MinD and MCD1 (Chen et al, 2018b; Zhang et al, 2021). It would be interesting to investigate whether the J-like domain could regulate the interaction between ARC6 and these Min system components in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since ARC3 is the core component of the Min system, the J-like domain is likely to regulate the interaction between ARC6 and other Min components as well. It has been reported that ARC6 interacts with both MinD and MCD1 (Chen et al, 2018b; Zhang et al, 2021). It would be interesting to investigate whether the J-like domain could regulate the interaction between ARC6 and these Min system components in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…ARC6 has been shown to bridge MCD1 to interact with FtsZ2, which may allow MCD1 to recognize the membrane-tethered Z ring and ultimately to regulate the positioning of the division machinery (Chen et al, 2018b). A recent study reported that ARC6 directly interacts with MinD1 (Zhang et al, 2021). The biological significance of such an interaction, however, is unsolved.…”
Section: Introductionmentioning
confidence: 99%